An Interoperability on the Internet of Things (IoT): A Review - Chaitali A. Chate; Sanjeev S. Sannakki; Vijay S. Rajpurohit (International Journal of Radio Frequency Innovations, 2024)
With technological advancement growing at a rapid rate, we are presented with numerous ways of connecting ourselves to the rest of the world. The Internet of Things, or IoT, is now a reality, even at the minuscule level. With ubiquitous computing, we can stay in constant communication with the outside world. As such there are several types of devices capable of monitoring, measuring, and sending data back and forth from the web. These various devices use different types of communication models; and data models are heterogeneous in nature, and are not interoperable. To have truly seamless communication between heterogeneous devices, an interoperable environment is necessary. We discuss the interoperability problem in IoT devices, and its related issues and identify the research gaps, present a problem statement, and propose objectives and methodology that serve as a guide for future work.
Keywords: Cybersecurity; Internet of Things; data analytics; interoperability; wireless sensor networks